Heat transfer enhancement by flexible printed circuit board's deformation. (May 2017) - Lim, C.H.; Abdullah, M.Z.; Azid, I.A.; Khor, C.Y.
Abstract: Flexible printed circuit board (FPCB) has started replacing rigid PCB in some electronic application. However, the deflection and heat transfer of FPCB caused by flow and thermal are far more crucial compared to rigid PCB. In the current study, effects of flow and thermal induced deflection were coupled in real time. The numerical modelling was executed using FLUENT and ABAQUS, coupled online by Mesh-based Parallel Code Coupling Interface (MpCCI). The numerical findings have been validated with experimental results. Rigid PCB with same thermal properties of FPCB has been compared. The findings showed that the deflection of the FPCB does help to increase the heat transfer of the PCB. Furthermore, models with different power of heat sources along with various Reynolds numbers ( Re ) had been studied. The results exhibited that the magnitude and the trend lines' pattern of deflection divided by characteristic length changes according to thermal power. It indicates both flow and heat have significant effect to the deflection and Nusselt number ( Nu ) of FPCB. Therefore, flow and thermal should be coupled at the same time for more realistic FPCB simulation under flow environment in operating condition.